2015
DOI: 10.2298/mpns1508240m
|View full text |Cite
|
Sign up to set email alerts
|

Articulation of speech sounds of Serbian language in children aged six to eight

Abstract: The most common disorder of articulation is distortion, while only substitution and substitution associated with distortion are less common. Omission does not occur in children from 6 to 8 years of age. Girls have slightly better quality of articulation. The articulatory disorders are more common in preschool children than in children who are in the first grade of primary school. The most commonly mispronounced sounds belong to the group of affricates and fricatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
2
2
0
2
Order By: Relevance
“…In this way a larger number of participants within the experimental group are boys (76.7%), while a larger number of girls are within the control group (56.7%) (Figure1.) The result shows that articulation speech disorders are more common in boys than in girls, as shown by other studies (10,11,12). The average age of sample participants in the E group was M=6.07+-0.5 years, and in the C group M=6.34+-0.46.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In this way a larger number of participants within the experimental group are boys (76.7%), while a larger number of girls are within the control group (56.7%) (Figure1.) The result shows that articulation speech disorders are more common in boys than in girls, as shown by other studies (10,11,12). The average age of sample participants in the E group was M=6.07+-0.5 years, and in the C group M=6.34+-0.46.…”
Section: Resultssupporting
confidence: 75%
“…The E group records 16.7% ambidextrous children, showing that this group has considerably more children without differentiated lateralisation, which indicates slow maturation of the structures and functions that determine movement lateralisation. While around 40% of children aged between 4 and 5 are weakly lateralised, this percentage drops to about 30% among those aged between 5 and 7 (11). The hand grip development level is another item recording a statistically significant difference between the E and the C group.…”
Section: Discussionmentioning
confidence: 93%
“…In other languages, such as Serbian, they observed that the phonemes with the greatest difficulty were affricates and fricatives, and the most common articulation disorder was distortion. (Mihajlovi et al, 2015).…”
Section: Article In Pressmentioning
confidence: 99%
“…Prethodna istraživanja u grupi ispitanika tipične populacije predškolskog i mlađeg školskog uzrasta takođe ukazuju da je najčešće izmenjen izgovor glasova iz grupa afrikata i frikativa (Mihajlović et al, 2015). Kod ispitanika s CP i LIO nisu pronađena istraživanja kvaliteta grupe glasova koja bi poslužila za komparaciju sa rezultatima ispitivanog uzorka istog kalendarskog uzrasta i na istom govornom području.…”
Section: Diskusijaunclassified
“…Naš ispitivani uzorak formiran je od učenika koji su u mlađem školskom dobu, a za taj period se navodi mirniji i ne tako buran razvoj artikulacionih sposobnosti, jer se nakon osme godine artikulacione navike ustaljuju i sve teže nadograđuju i upotpunjuju (Bernthal et al, 2016; Mihajlović et al, 2015). Najmerodavnijim za komparaciju s našim smatramo istraživanje o kvalitetu glasovnog fonda sprovedeno u uzorku dece koja govore srpski jezik.…”
Section: Diskusijaunclassified